Multi-layer relationships between psychological symptoms and life adaptation among humidifier disinfectant survivors - Lee, Min Joo; Lee, Hun-Ju; Ko, Hyeyun; Ryu, Seung-Hun; Lee, Sang Min (Frontiers in Psychology, 2022)
This study was designed to investigate the multi-layer relationships between psychological symptoms and adaptive functioning in survivors of the Humidifier catastrophe in South Korea caused by chemical toxic substances. Specifically, this study aimed to explore how psychological symptoms affect actual interpersonal relationships and job adjustment with two variable sets, six internalizing and externalizing subscales, and three adaptation subscales. A total of 224 survivors recruited from a program to support humidifier disinfectant survivors by the government participated in this study. The age range of the participants was 18–73 years (M=42.23, SD =10.90), 37.1% (n=83) were male, and 62.9% (n=141) were female. The participants responded to the Adult Self-Report (ASR) of the Achenbach System of Empirically Based Assessment (ASEBA). A Canonical Correlation Analysis (CCA) generated three unique patterns in the relationships between psychological symptoms and adaptive functions. Humidifier disinfectant survivors in the first pattern were more vulnerable to psychological symptoms and showed maladaptive functioning in life. Survivors in the second pattern showed intrusive behaviors and appeared to be adaptive in relationships with friends. Finally, survivors in the third pattern showed aggressive behaviors and reported poor partner relationships while showing good relationships with friends. The practical implications of the interventions are also discussed.